The Exiles of Marcel Duchamp (Massachusetts; MIT Press, 2012)
Exile as the dominant fact of Marcel Duchamp's life and artistic practice: how the "spirit of expatriation" and sense of dislocation infused the mobile objects and disjunctive spaces of Duchamp's readymades and experimental exhibition installations.
English
Keywords: N5300-7418 Visual Arts- History